PRAWNE UWARUNKOWANIA ROZWOJU FUNDUSZY INWESTYCYJNYCH LOKUJĄCYCH W NIERUCHOMOŚCI - Redakcja (Wydział Prawa i Administracji UAM, 2002)
In the current conditions one could hardly expect a rapid establishment and development of investment funds investing in real estate in Poland, not only due to the lack of relevant legal regulations. Among some further causes there are some technical obstacles in dealing in real estate as well as an often unclear legal status of real property. Besides, the high minimal allowed asset value is an additional deterrent. Currently, this minimal value is 0.5 billion zl for an investment of 30 - 40 million zł. This condition follows the requirement to maintain an appropriate level of investment diversification in order to reduce the risks involved. The only specialist closed investment fund that has ever attempted to invest in real estate in Poland failed to collect even 10% of the amount. Another obstacle in developing specialist closed investment funds investing in real estate is also the relatively short time of keeping shares by Polish investment fund shareholders (in Germany the median of keeping open investment fund shares being 7 years). This can impede selling off specialist closed investment fund shares and in the case of open funds it also implies the need to maintain a high share of liquid securities (especially T-bonds) with a view to securing possible obligations involved in share redemption. This can in consequence reduce the investment return rate. When drafting legislation concerning funds investing in real estate (especially open ones) one should focus in particular upon their investment target. Transparency of the real estate market is veiy limited, as there is no full information on the deals handled on this market; also, the object of the deals, i.e. real estate ownership, is atypical. On the market it is dealt in ownership rights, which are highly individualized and which are priced on the basis of a number of factors, such as the location, legal and physical condition, or local land development plan, all of which add up to the individual value of each property. One should therefore consider limiting the investment target of future open real estate funds only to managing and reaping profits from owned real property rather than allow speculative transactions, which should be allowed only for specialist closed investment funds. Collective real estate investment institutions are an important element of developed capital markets. It is hard not to appreciate their impact upon the development of real estate market and due to a relatively low risk involved in investing in this market, such institutions are a significant long-term saving instrument (especially toward pension). One should hope that the legislator will soon give a green light to the investments in question not only for smaller investors (for whom open real estate funds will be available) but also to e.g. open pension funds. Under the current law open pension funds are banned from investing not only directly in real estate but also in specialist closed investment fund shares.
LEGAL CONDITIONS OF DEVELOPING INVESTMENT FUNDS WHICH INVEST IN REAL ESTATE